Evidence-based Teaching Practices in Physics: An Overview on Authentic Teaching and Learning (Journal of Nepal Physical Society, 2024)
Learning is inherently a social process as outlined by the theory of constructivism. Learners construct knowledge via active participation and experience. Meaningful learning requires multiple means of engagement, representation of materials, and assessment. The current challenges in physics teaching-learning are understanding of the learning mechanism, designing of proper instructional materials, and use of student-engagement strategies that help them in long-term retention of the concepts. Pedagogical research shows that the teaching-learning process should be learner-centered where the learners will take ownership of their learning. This paper provides a review of various Research-Based Instructional Strategies (RBIS) designed to enhance physics education through learner-centered and authentic teaching practices. The literature shows that the use of RBIS fosters a more engaging learning environment, students’ deeper understanding of the material, and higher retention rates. This paper also explores the limitations of traditional lecture-based pedagogy and emphasizes the need for active learning approaches. Furthermore, it addresses challenges in implementing RBIS, such as large class sizes, time constraints, instructional resource availability, and so on. Finally, we summarize our effort to disseminate the RBIS within the Nepali physicists’ community.